THE EFFECTS OF GIVING Citrus hystrix SOLUTION on ERYTHROCYTES PROFILE of pangasius hypophthalmus - Chairani Irawan; Morina Riauwaty; Iesje Lukistyowati (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
ABSTRACTCitrus hystrix is an essential oil producing plant. In addition to essential oils, there are several ingredients of Citrus hystrix as an antibacterial agent, namely: vitamin C, flavonoids, tannins and alkaloids. This research was conducted on June until August 2019. The aims of this research was to get obtain information about the effect of giving a solution of Citrus hystrix to the erythrocyte image of conjoined Pangasius hypophthalmus and find out the best dosage for the prevention of MAS (Motile Aeromonas Septicaemia) disease, seen from the total erythrocytes, hemoglobin, hematocrit, and morphology of erythrocyte patchouli fish (Motile Aeromonas Septicaemia). The method used is an experimental method with a completely randomized design (CRD), one factor with 5 treatment and three raplication of KN: (without immersed with Citrus hystrix solution and without infected by Aeromonas hydrophila) KP: (without immersed with Citrus hystrix solution and infected by Aeromonas hydrophila.) P1: (1200 ppm), P2: (1500 ppm), P3: (1800 ppm). immersed of Citrus hystrix solution was carried out four times, namely on days 7,14,21 and 28, soaking was carried out for 2 minutes. Then on the 31st day a challenge test was carried out with Aeromonas hydrophila bacteria with a density of 108 CFU / ml of 0.1 ml /fish. The results showed that immersed of fish with a solution of Citrus hystrix gave effect to the erythrocyte image of conjoined Pangasius hypophthalmus. The best dosage is P2 1500 ppm treatment seen from total erythsoit 172.67 x 104 cells/mm3, hematocrit value 31.33% and hemoglobin value 6.93 g/dl. Siamese Pangasius hypophthalmus life reaches 100%. The quality of water obtained during the study were temperatures ranging from 27.3 - 28 oC, pH 6-7, DO 3.2 - 4.7 mg/L and Ammonia 0.02 mg/L.Key word :Citrus hystrix, Catfish, Aeromonas hydrophila, immertion,erythrocyte,